Answer:
Step-by-step explanation:
Area of square= S^2
S = 7/8
= 7/8 ^ 2
= 49/64
Answer:
Equation: ![30=2(x-2)+2(2x+3)](https://tex.z-dn.net/?f=30%3D2%28x-2%29%2B2%282x%2B3%29)
Step-by-step explanation:
By definition, the perimeter of a figure can be calculated by adding the lenghts of its sides.
Knowing this, you can write the following equation:
<em> [Equation 1]</em>
According to the data given in the exercise, the perimeter in feet of the fighter is:
![P=30](https://tex.z-dn.net/?f=P%3D30)
Therefore, you can substitute this values into<em> [Equation 1]:</em>
![30=2(x-2)+2(2x+3)](https://tex.z-dn.net/?f=30%3D2%28x-2%29%2B2%282x%2B3%29)
Finally, you must solve for "x" in order to find its value. This is:
![30=6x+2\\\\30-2=6x\\\\\frac{28}{6}=x\\\\x=\frac{14}{3}](https://tex.z-dn.net/?f=30%3D6x%2B2%5C%5C%5C%5C30-2%3D6x%5C%5C%5C%5C%5Cfrac%7B28%7D%7B6%7D%3Dx%5C%5C%5C%5Cx%3D%5Cfrac%7B14%7D%7B3%7D)
The exponential equation of the model is A(t) = 2583 * 0.88^t and the multiplier means that the number of new cases in a week is 88% of the previous week
<h3>The function that models the data</h3>
The given parameters are:
New, A(t) = 2000
Rate, r = 12%
The function is represented as:
A(t) = A * (1 - r)^t
So, we have:
2000 = A * (1 - 12%)^t
This gives
2000 = A * (0.88)^t
2 weeks ago implies that;
t = 2
So, we have:
2000 = A * 0.88^2
Evaluate
2000 = A * 0.7744
Divide by 0.7744
A = 2583
Substitute A = 2583 in A(t) = A * 0.88^t
A(t) = 2583 * 0.88^t
Hence, the exponential equation of the model is A(t) = 2583 * 0.88^t
<h3>The interpretation of the multiplier</h3>
In this case, the multiplier is 88% or 0.88
This means that the number of new cases in a week is 88% of the previous week
Read more about exponential equation at
brainly.com/question/2456547
#SPJ1
I think the question 23 is e.
Answer:
(-2,3)
Step-by-step explanation:
For the point to be 2/3 of the way; it means it divides AB into the ratio 2 to 1
Now, we can use the internal section formula to get the coordinates of this point
(x,y) = (nx1 + mx2)/(m + n), (ny1 + my2)/(m + n)
where (m,n) = (2,1)
(x1,y1) = (-4,-1)
(x2,y2) = (5,5)
(x,y) = (1(-4) + 2(-1)/(1+2), (1(-1)+2(5)/(1+2)
(x,y) = (-4-2)/3, (-1 + 10)/3
(x,y) = (-2,3)